2015
DOI: 10.1016/j.jcat.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic reduction of NO with ethanol on Au/TiO2

Abstract: The effect of illumination on the surface interaction and the reaction between NO + C 2 H 5 OH was investigated on Au/TiO 2 catalyst. By means of Fourier transform infrared spectroscopy, the formation of absorption bands at $2180 and $2210 cm À1 was observed. The first was attributed to the NCO species locating on Au particles, and the second one to NCO residing on the TiO 2 support. While the thermal reaction between NO and C 2 H 5 OH on Au/TiO 2 catalyst occurred with measurable rate only at and above 473-52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Photocatalytic reaction was followed in the same way as described in our previous papers [35], equipped with a 500 W medium pressure mercury vapor lamp (TQ 718, Heraeus Noble light, Germany) as a light source. In some experiments we applied a 15 W germicide lamp, which emits predominantly in the wavelength of 250e440 nm, and its maximum intensity is at 254 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photocatalytic reaction was followed in the same way as described in our previous papers [35], equipped with a 500 W medium pressure mercury vapor lamp (TQ 718, Heraeus Noble light, Germany) as a light source. In some experiments we applied a 15 W germicide lamp, which emits predominantly in the wavelength of 250e440 nm, and its maximum intensity is at 254 nm.…”
Section: Methodsmentioning
confidence: 99%
“…For FTIR studies a mobile IR cell housed in a metal chamber was used [35]. Infrared spectra were recorded with a Biorad (Digilab.…”
Section: Methodsmentioning
confidence: 99%
“…Common and effective route to enhance the spe cific surface is structuring layers with various nanostructures on TiO 2 . [111] Tang Pds/TiO 2 Anatase TiO 2 nanoparticles Successive ionic layer adsorption and reaction method [189] Au/Ag/TiO 2 NWs Commercial anatase TiO 2 particles Hydrothermal and photodeposition [190] g-C 3 N 4 /G/TiO 2 TiO 2 paste Self-assembly photochemical reduction [191] Cds/TiO 2 TiO 2 NWs Successive ionic layer adsorption and reaction method [192] N/TiO 2 NRs TiO 2 NWs Hydrothermal method [193] Cds/TiO 2 FTO-coated glass slides One-step electrodeposition technique [194] CdSe/TiO 2 FTO-coated glass Electrospinning pyrolysis and chemical bath deposition [195] Al(H 2 PO 4 ) 3 /TiO 2 Titanium fluoride Spray method [196] Ag/TiO 2−x FTO substrates Photochemical reduction process and postannealing [197] BiVO 4 /TiO 2−x Al(H 2 PO 4 ) 3 Two-step hydrothermal [198] ZnO/TiO 2 TiO 2−x Sol-gel deposition and hydrothermal [199] RGO/Ag 2 S/TiO 2 TiO 2−x Hydrothermal and ionexchange [200] RGOT aerogel ITO One-step hydrothermal [201] ZnSe/Au/TiO 2 NTs GO Two-step anodization, microwave-assisted chemical reduction and in situ deposition [202] Bi (Figure 10k,l). Still problems like accuracy controlling of the size of particles, connectivity, and distribu tion between the interfaces of NPs and TiO 2 NBs remain set tled.…”
Section: Surface Modification With Enlargement Of the Accessible Surfmentioning
confidence: 99%
“…Thus, on one hand, it is necessary to create sufficient reactive sites for enlarging the surface area for better photocatalytic efficiency. Common and effective route to enhance the specific surface is structuring layers with various nanostructures on TiO 2 . Tang et al produced a nanoflake–nanoparticle compound hierarchical TiO 2 nanostructure with high photocatalytic performance ( Figure k,l).…”
Section: Strategies In Improving Nanostructured Tio2 Based Materials mentioning
confidence: 99%
“…We expect that the Au in nanosize (1-3 nm) deposited on n-type semiconducting oxides might be able to activate the rather inert CO 2 and induces its thermal and photoreactions with H 2 even at low pressure. Recently, it was found the Au/TiO 2 is a very effective catalyst even for the photoinduced reactions of NO + C 2 H 5 OH and in the decomposition of several organic compounds at room temperature [24]. As regards the activation of CO 2 , recently we found that the deposition of K on Au(1 1 1) single crystal leads to the formation of negatively charged CO 2 and its dissociation even above 300 K [25].…”
Section: Introductionmentioning
confidence: 95%